Creating a blue ocean strategy for an e-trading start-up - Drake, Darren (My University, 2025)
The study set out to discover a blue ocean strategy for HitchPin, an e-commerce solution for agricultural commodities. The study reviewed the evolution of e-commerce and its relevance to agriculture. The review indicated that the increase in automation of selling and buying activities on the internet has opened opportunities for a wide variety of market stakeholders to transact with people they would otherwise never have encountered. The review showed that more than 80% of U.S. cattle farms were small, having less than 100 head of cattle. This observation provides a window for HitchPin to look beyond the current boundary defined by the industry, i.e., large cattle ranchers. We estimated that having access to less than 1% of this market, where they sell only 50 head could be profitable with the appropriate value innovation. The overall objective of the research was to develop a value innovation strategy for HitchPin. The study successfully develops a value innovation strategy, which calls for the company to move into a blue ocean space by focusing attention on small producers with less than 100 head of cattle per year. This focus will reduce servicing costs significantly, especially since our analysis showed that the company does not need more than 300 farmers to post a positive net present value.
Keywords: Blue ocean strategy; E-commerce; Value innovation strategy; HitchPin